Trends of karyotype evolution in the Neotropical long-legged crickets Phalangopsidae (Orthoptera, Grylloidea) - Timm, Vítor Falchi; Martins, Luciano De Pinho; Acosta, Riuler Corrêa; Szinwelski, Neucir; Pereira, Marcelo Ribeiro; Da Costa, Maria Kátia Matiotti; Zefa, Edison (Zootaxa, 2021)
Phalangopsids are a diverse group of crickets found in all tropical and subtropical regions, and includes 1044 valid species. Up to now, only 22 species were studied cytologically, with the chromosome number ranging from 2n = 11 to 2n = 21. In this paper we studied the chromosomes of 12 phalangopsid species from different Brazilian biomes (eight of them reported for the first time), and we traced some trends on chromosomal derivation in this group, based on chromosome morphology and fundamental number. We found that in the phalangopsid species the karyotype concentrates a large amount of metacentric chromosomes, the result of successive centric fusions over evolutionary time. Moreover, pericentric inversions and translocations have been also important in the chromosomal derivation of these crickets.